PENGARUH ONLINE CUSTOMER REVIEW, KUALITAS PRODUK DAN CUSTOMER EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MAYBELLINE PADA MAHASISWI DI UNIVERSITAS ISLAM DARUL ‘ULUM LAMONGAN - Bilgies, Ana Fitriyatul; Fauziyah, Nurul; Sulistyowati, Anjar (Pro-fit, 2024)
ABSTRACT The purpose of this study was to determine the effect of online customer reviews, product quality and customer experience on purchasing decisions for Maybelline cosmetics for female students at Darul ‘Ulum Lamongan Islamic University. The population in this study amounted to 1.519 female students, with a total sample of 94 respondents. The sampling technique used is Purposive Sampling, the analytical method used for this research is deskriptif analys, validity test, reability test, multiple liniear regression test, coefficient of determination test, classic assumption test,t test, f test,. The result of the t test of this study indicate that the online customer reviews variable obtained atcount value of 3.274>1.661, the product quality variable obtained atcount value of 4.771>1.661, the customer experience variable obtained atcount value of 7.241>1.661, and the f test result for the online customer reviews, product quality and customer experience on purchasing decisions obtained Fcount>Ftable or 75.021>2.705, and adjusted r squared value of 0.705 or 70.5%. This show that the variables online customer reviews, product quality and customer experience have a partial and simultaneous effect on purchasing decisions, and the remaining 29.5% is influenced by other variables not examined in this study. Keyword: Customer Review, Product Quality, Customer Experience